Application of metal organic framework material to removal of trace benzene in cyclohexane

By using the metal organic frame structure of Zn-Ade-TCPE material, the problem of removing trace benzene in cyclohexane is solved, and efficient and low-energy consumption cyclohexane purification is achieved, with a purity of more than 99.9%.

CN119406385AActive Publication Date: 2025-02-11BEIJING UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411744796.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-11
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove trace amounts of benzene from cyclohexane, and the traditional methods consume high energy and have low purity, which cannot meet the needs of industrial production.

Method used

The metal organic frame material prepared from Zn(II)-based metal organic frame material Zn-Ade-TCPE is used to achieve efficient removal of trace benzene in cyclohexane through its unique three-dimensional frame structure and pore structure.

Benefits of technology

Zn-Ade-TCPE material exhibits highly selective adsorption of benzene molecules under both gas and liquid phase conditions, which can effectively capture and remove benzene under low concentration conditions, achieving high purity separation of cyclohexane, with a purity of 99.9%. above.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406385A_ABST
    Figure CN119406385A_ABST
Patent Text Reader

Abstract

The invention belongs to metal organic coordination polymer materials, belongs to the technical field of crystalline materials, and particularly relates to application of a metal organic framework material to removal of trace benzene in cyclohexane. The metal organic framework material Zn-Ade-TCPE is synthesized from 4, 4 ', 4' ', 4 '''-(ethylene-1, 1, 2, 2-tetrayl) tetrabenzoic acid, adenine and zinc nitrate hexahydrate under a solvothermal condition. The Zn-Ade-TCPE has a slit-shaped pore channel structure, and the selective adsorption capacity of the material to benzene molecules is improved due to the pore channel structure characteristic. In addition, atoms or groups such as nitrogen and oxygen on the hole wall of the Zn-Ade-TCPE generate multiple interaction on the adsorbed benzene molecules, so that the affinity of the nitrogen atoms or groups and the oxygen atoms or groups is improved. Through the synergistic effect of the factors, the material shows excellent benzene / cyclohexane separation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to metal organic coordination polymer materials, belongs to the technical field of crystalline materials, and particularly relates to application of a metal organic framework material in removing trace benzene in cyclohexane. Background Art

[0002] Benzene and cyclohexane are two important chemicals in the petrochemical industry, and their separation is crucial in various industrial processes. However, the separation of these two compounds faces great challenges due to their close boiling points (benzene: 80.1°C, cyclohexane: 80.7°C), similar molecular sizes, and easy formation of azeotropes, which makes traditional distillation methods inefficient and energy-intensive. Cyclohexane is widely used in the production of adipic acid and caprolactam, which are precursors of nylon. The production of high-purity cyclohexane is crucial for the production of nylon, as well as the production of some pharmaceutical intermediates and high-purity solvents. On the other hand, benzene is a Class I carcinogenic compound, and even very low concentrations of benzene in cyclohexane can cause harm to public health and the environment. In industry, cyclohexane is generally produced by catalytic hydrogenation of benzene. The removal of a very small amount of unreacted benzene in the cyclohexane product is technically challenging, requiring complex processes and complicated process operations to achieve, and extremely high energy consumption. To address this problem, it is of great significance to develop efficient and energy-saving materials and methods.

[0003] An ideal adsorbent for removing trace benzene from cyclohexane should have at least two characteristics: high benzene / cyclohexane adsorption selectivity and high adsorption capacity for trace benzene in benzene / cyclohexane mixtures. However, most reported adsorbents with high benzene / cyclohexane adsorption selectivity have low adsorption capacity for benzene at low partial pressures. Without high adsorption selectivity, even if they have high benzene adsorption capacity at low partial pressures in single-component adsorption, their performance in the separation of benzene / cyclohexane mixtures still cannot meet practical needs. No adsorbent has been found to meet both of the above requirements.

[0004] Among the various crystalline materials reported for this separation, MOFs have attracted much attention due to their high surface area, tunable pore size, and multiple functionalities. Some MOFs, such as MFM-300(Sc), Mn-DHBQ, and MAF-stu-13, have shown significant selectivity and adsorption capacity for benzene in cyclohexane. However, the removal performance of MOFs adsorbents for extremely low concentrations of benzene in cyclohexane, especially under liquid phase conditions, has rarely been studied and confirmed. Summary of the invention

[0005] In view of the problems of difficulty in separating benzene and cyclohexane, high energy consumption and low purity in the prior art, the present invention provides an application of a metal organic framework material in removing trace benzene from cyclohexane. The MOF exhibits a molecular sieve effect in the separation of benzene and cyclohexane, and can be used for the capture and removal of low-concentration benzene to achieve efficient purification of cyclohexane.

[0006] The present invention is achieved through the following technical solutions: Application of a metal-organic framework material in removing trace benzene from cyclohexane.

[0007] Furthermore, the metal organic framework material is a Zn (II) based metal organic framework material Zn-Ade-TCPE constructed by mixed ligands, and the chemical formula is C 116 H 96 N 14 O 30 Zn 7, The yellow block crystalline material is prepared by solvent thermal reaction of organic ligand H4TCPE, adenine and Zn(NO3)2·6H2O, wherein H4TCPE is 4,4',4'',4'''-(ethylene-1,1,2,2-tetrayl)tetrabenzoic acid, with the molecular formula C 30 H 20 O8.

[0008] Furthermore, the molar ratio of adenine, H4TCPE and Zn(NO3)2·6H2O is 1.5:1:2.5, the volume ratio of DMA and water in the mixed solvent is 1:1, and the volume (mL) of the solvent used per millimole of the organic ligand H4TCPE is 1:60.

[0009] Furthermore, the solvent thermal reaction temperature is 120° C. and the reaction time is 24 hours.

[0010] Furthermore, the metal organic framework material can achieve the removal of trace benzene in cyclohexane in gas phase and liquid phase.

[0011] Furthermore, the metal organic framework material can be recycled.

[0012] Further, from the perspective of crystal structure, the Zn-Ade-TCPE belongs to the orthorhombic system, and the space group is Pcca , the unit cell parameters are V = 14341(8) Å 3 , a = 32.5934(11) Å, b = 13.5555(4) Å, c= 32.4592(10) Å. The Zn-Ade-TCPE has a three-dimensional framework structure, which includes chain units formed by the coordination of Zn atoms and N atoms on the adenine ring, and the chain units are connected by deprotonated H4TCPE to form a three-dimensional framework structure. There are two types of holes in the three-dimensional framework structure of Zn-Ade-TCPE, and the holes are connected by extremely narrow pore openings of about 4.2×6.7Å, which are slit-shaped. Thinner benzene molecules can pass through, and thicker cyclohexane is inhibited from entering the holes, thereby achieving highly selective separation of the two.

[0013] Furthermore, the method for activating the Zn-Ade-TCPE material is as follows: washing the sample with DMA solvent, then immersing it in methanol solvent, performing solvent exchange for 3-4 times, and then drying the sample immersed in methanol at 60°C, and degassing at 120°C for 8 hours to obtain a dry sample of the material desolvated.

[0014] Furthermore, the purity of cyclohexane after separation by Zn-Ade-TCPE reaches over 99.9%.

[0015] Beneficial technical effects of the present invention: The present invention provides a metal organic framework (MOF) adsorbent which exhibits a molecular sieve effect for benzene and cyclohexane. The MOF has extremely high benzene adsorption capacity under low pressure conditions, while the adsorption amount of cyclohexane is extremely low. Zn-Ade-TCPE performs well in the application of selective adsorption of benzene in cyclohexane, whether in gas phase or liquid phase, even when the concentration of benzene is as low as ppm. The MOF has a record high benzene / cyclohexane adsorption selectivity (216, 723 and 1027) in a liquid mixture of benzene and cyclohexane (v / v = 1:1, 1:10 and 1:20), and can effectively capture benzene molecules even in the gas phase at low partial pressure (e.g., 2.49 mmol / g at 8.2 Pa) or at low concentrations in liquid cyclohexane (e.g., 128 mg / g at 20 ppm). Using this adsorbent, a simple room-temperature stripping step can remove trace amounts of benzene (1000 ppm) from liquid cyclohexane and produce cyclohexane with a purity of more than 99.999%.

[0016] The excellent benzene / cyclohexane separation performance of Zn-Ade-TCPE is attributed to its unique pore structure and its strong interaction with benzene molecules. Zn-Ade-TCPE is prepared from two ligands: zinc ions, adenine and 4,4',4'',4'''-(ethylene-1,1,2,2-tetrayl)tetrabenzoic acid (H4TCPE). The resulting three-dimensional framework structure has two types of holes, and the windows between the holes are extremely narrow and slit-shaped. The ability of Zn-Ade-TCPE to adsorb benzene molecules from cyclohexane with high selectivity is attributed to this unique pore structure feature on the one hand, and to its rich interactions with benzene molecules on the other hand. The micropore walls composed of adenine can form π-π stacking and multiple interactions such as NH···π with benzene molecules, which enhances the affinity between the two. The above two reasons together lead to the high performance of Zn-Ade-TCPE in capturing benzene molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the SEM image of the Zn-Ade-TCPE crystal prepared in Example 1.

[0018] Figure 2 The structure and composition of Zn-Ade-TCPE: (a) molecular structure of the ligand; (b) 1D chain unit; (c) three-dimensional framework structure of Zn-Ade-TCPE. Zn is green; O is red; N is blue; C is black.

[0019] Figure 3 Schematic diagram of the pore distribution of Zn-Ade-TCPE.

[0020] Figure 4 This is the thermogravimetric analysis diagram of Zn-Ade-TCPE.

[0021] Figure 5 Powder diffraction patterns of Zn-Ade-TCPE samples and samples after various treatments and tests.

[0022] Figure 6 The adsorption isotherms of benzene and cyclohexane on Zn-Ade-TCPE.

[0023] Figure 7 This is the five-cycle adsorption isotherm test diagram of benzene on Zn-Ade-TCPE.

[0024] Figure 8 Benzene and cyclohexane vapor breakthrough curves for Zn-Ade-TCPE (nitrogen stream containing about 0.51% benzene (Bz) and about 4.75% cyclohexane (Cy) vapor as inlet gas).

[0025] Fig. 9GC-FID chromatogram of benzene and cyclohexane in the inlet or outlet gas (nitrogen flow containing about 0.51% benzene (Bz) and about 4.75% cyclohexane (Cy) vapor as the inlet gas).

[0026] Fig.10 The vapor breakthrough curves of benzene and cyclohexane of Zn-Ade-TCPE (benzene and cyclohexane 100 and 900 ppm; 500 and 500 ppm).

[0027] Fig.11 GC-FID chromatograms of benzene and cyclohexane in the inlet or outlet gas (inlet gas is 100 and 900 ppm for benzene and cyclohexane).

[0028] Fig.12 Figure 2 shows the concentration of benzene (Bz) in the outlet gas monitored by GC-FID during the breakthrough experiment (the concentrations of benzene and cyclohexane in the inlet gas were 100 and 900 ppm, respectively).

[0029] Fig.13 Mass spectrometric signal intensity of benzene and cyclohexane released by heating the MOF sample at 120 °C with nitrogen flow after the breakthrough experiment (the concentrations of benzene and cyclohexane in the inlet gas of the breakthrough experiment were 500 and 500 ppm, respectively).

[0030] Fig.14 The adsorption of substances on Zn-Ade-TCPE 1 H NMR spectrum.

[0031] Fig.15 This is a comparison diagram of the adsorption selectivity of liquid phase benzene / cyclohexane of Zn-Ade-TCPE.

[0032] Fig.16 is the adsorption of substances on Zn-Ade-TCPE sample after five consecutive adsorption experiments. 1 H NMR spectrum.

[0033] Fig.17 This is the adsorption isotherm of Zn-Ade-TCPE for benzene in cyclohexane in liquid phase (the data are the average of three groups of experiments).

[0034] Fig.18 Figure 3. Changes of benzene concentration in cyclohexane over time during liquid phase adsorption (inset: zoomed-in view of the last 200 minutes of data). DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0036] Example 1 Preparation of Zn-Ade-TCPE Zn(NO3)2·6H2O (2.5 mmol), H4TCPE (500 mg, 1.0 mmol) and adenine (200 mg, 1.5 mmol) were dissolved in a mixture of 40 mL of water and 40 mL of dimethyl alcohol (DMA). After ultrasonic treatment, the solid was completely dissolved. The solution was then transferred to a 100 mL autoclave and reacted in an oven at 120°C for 24 hours. After the reaction was completed, it was cooled to room temperature, and the product Zn-Ade-TCPE crystalline sample was separated by centrifugation and washed with DMA, and then immersed in methanol solvent, and the solvent exchange was continued for 3-4 times. The exchanged crystalline sample was transferred to a fresh methanol solvent. The SEM image of the Zn-Ade-TCPE crystals prepared in Example 1 is shown in FIG. Figure 1 shown.

[0037] A single crystal sample of suitable size and high crystallinity prepared in Example 1 was selected, and diffraction data was collected using a single crystal diffractometer at 220K. The crystal structure was then refined using the structure analysis software SHELX. The specific crystal data are shown in Table 1.

[0038] The crystal data of Zn-Ade-TCPE are as follows: Empirical formula <![CDATA[C 116 H 96 N 14 O 30 Zn7]]> Measurement temperature 220K Crystal system orthorhombic Space group (Å) 32.5934(11) (Å) 13.5555(4) (Å) 33.4592(10) (°) 90 (°) 90 (°) 90 <![CDATA[Volume(Å 3 )]]> 14341.1(8) Z 4 <![CDATA[Calculated density(g / cm 3 )]]> 1.215 Independent reflections (>()) <![CDATA[5360 [R int = 0.0661]]]> Reflections collected 53892 <![CDATA[Goodness-of-fit on F 2 ]]> 1.042 <![CDATA[ R 1 a , wxya 2 b [ I >2 σ ( I )]]]> <![CDATA[R1 = 0.0719, wR2 = 0.1963]]> <![CDATA[ R 1 a , wxya 2 b (all data)]]> <![CDATA[R1 = 0.0997, wR2 = 0.2114]]> The structure of the Zn-Ade-TCPE crystal is shown in Figure 2 The structure of Zn-Ade-TCPE includes chain units formed by the coordination of Zn atoms and N atoms on the adenine ring, and the chain units are connected by deprotonated H4TCPE to form a three-dimensional framework structure.

[0039] The three-dimensional framework structure of Zn-Ade-TCPE has a hierarchical pore structure, with large pores and small pores connected alternately to form an interlaced cavity structure. Figure 3 The interface of the macropore cavity is extremely narrow, about 4.25×6.73Å, which allows thinner benzene molecules to pass through and inhibits thicker cyclohexane from entering the pore, thus achieving highly selective separation of the two.

[0040] Figure 4 The thermogravimetric analysis (TGA) diagram of Zn-Ade-TCPE shows that Zn-Ade-TCPE has high thermal stability, and no obvious collapse of the MOF framework structure is observed before 350°C. The mass loss before 200°C is presumed to be the removal of the guest molecules coordinated by the pores.

[0041] Figure 5 This is the powder diffraction pattern of Zn-Ade-TCPE, which shows that the Zn-Ade-TCPE structure has good stability, maintains good crystallinity after adsorption / penetration and various treatments, and the structure does not collapse significantly.

[0042] Example 2 Static Vapor Adsorption Test Before the adsorption test, the sample soaked in methanol obtained in Example 1 was dried at 60°C and degassed at 120°C for 8 hours to obtain a dry sample of the material desolventized. 50-60 mg of the activated sample was placed in an adsorption tube and connected to the adsorption instrument for adsorption isotherm test and adsorption cycle test.

[0043] The vapor adsorption isotherms of benzene and cyclohexane were measured on Zn-Ade-TCPE at 298 K. The results are shown in Figure 6 The Zn-Ade-TCPE has a high adsorption capacity for benzene in the entire pressure range, while the adsorption capacity for cyclohexane is almost negligible (see Figure 6 a). at 12.4 kPa (0.95 P / P 0 , P 0 = 13.019 kPa), the adsorption of cyclohexane was only 0.23 mmol / g, and only the adsorption occurred on the outer surface. In contrast, at low pressure (<0.01 kPa), the adsorption of benzene increased sharply (see Figure 6 b). At 8.2Pa (6.4×10 −4 P / P 0 , P 0 = 12.695 kPa), the adsorption amount of benzene reached 2.49 mmol / g, and as the pressure approached the saturation pressure (12.2 kPa, 0.95 P / P 0 ), the adsorption amount gradually increased to 3.79mmol / g. This indicates that Zn-Ade-TCPE has a high affinity for benzene and a strong interaction with benzene molecules. Its extremely low adsorption amount for cyclohexane indicates that Zn-Ade-TCPE has an extremely weak interaction with cyclohexane.

[0044] In addition, the benzene adsorption of Zn-Ade-TCPE is completely reversible. By measuring its benzene adsorption isotherm five times and reactivating the MOF sample by vacuum heating at 120 °C in each cycle, the amount of benzene adsorbed remains essentially unchanged (see Figure 7 ). The static vapor adsorption experimental results show that Zn-Ade-TCPE has a high potential in the separation of benzene and cyclohexane vapors.

[0045] Example 3 Dynamic penetration experiment Before the penetration test, the sample soaked in methanol obtained in Example 1 was dried at 60°C and degassed at 120°C for 8 hours to obtain a dry sample of the material after solvent removal. 30-200 mg of the activated sample was placed in a penetration tube and connected to the penetration device for testing.

[0046] A nitrogen stream containing about 0.51% benzene and about 4.75% cyclohexane vapor (partial pressure ratio) was passed through a quartz column packed with a Zn-Ade-TCPE sample. Cyclohexane vapor immediately penetrated the Zn-Ade-TCPE column, but the retention time of benzene was as long as about 520 min / g (see Figure 8 ), the corresponding benzene adsorption amount is about 1.18 mmol / g. The purity of cyclohexane in the outlet gas exceeds 99.99% at 300 min / g as determined by gas chromatography-flame ionization detector (GC-FID) (see Fig. 9 a, b).

[0047] Similar breakthrough curves were obtained when the content of benzene and cyclohexane vapor in the inlet gas was changed, even down to the ppm level (see Fig.10 a, b). When the concentrations of benzene and cyclohexane were 100 and 900 ppm, respectively, the Zn-Ade-TCPE sample could still capture trace amounts of benzene vapor, with a capture capacity of up to about 1.34 mmol / g (beginning to penetrate at about 15,000 min / g), but almost no cyclohexane was adsorbed (see Fig.10 b). GC-FID analysis results show that benzene was not detected in the outlet gas before 5000 min / g, and then the concentration of benzene increased slightly, ranging from 0.07 ppm to 0.21 ppm at 6000 min / g to 12000 min / g, and 6.16 ppm at 13000 min / g (see Fig.11 a, b and Fig.12 ). Before 12000 min / g, the purity of cyclohexane in the outlet gas was higher than 99.97%. By heating the Zn-Ade-TCPE sample at 120°C in a nitrogen stream, the adsorbed benzene (containing a small amount of cyclohexane) can be recovered (see Fig.13 ). These results confirm that Zn-Ade-TCPE is able to effectively separate realistic vapor mixtures of benzene and cyclohexane at room temperature even in the low pressure range.

[0048] Example 4 Liquid phase separation experiment Since the separation of benzene and cyclohexane is mainly carried out in the liquid phase, the performance of Zn-Ade-TCPE in liquid phase benzene / cyclohexane separation was tested.

[0049] Before the liquid phase separation experiment, the sample immersed in methanol obtained in Example 1 was dried at 60° C. and degassed at 120° C. for 8 hours to obtain a dry sample of the material desolventized. The Zn-Ade-TCPE sample was placed in a liquid mixture of benzene and cyclohexane with a volume ratio of 1:1, 1:10, and 1:20.

[0050] After shaking at room temperature for 6 h, the MOF samples were collected by filtration and dried at 40 °C to remove residual liquid. The molecular guests adsorbed by MOF were extracted by deuterated methanol and then 1 H NMR spectroscopy analysis, the results obtained are as follows Fig.14 As shown. There is a strong peak at 7.3 ppm, corresponding to the hydrogen atoms of benzene, while the peak of the hydrogen atoms of cyclohexane at 1.5 ppm is almost undetectable. The molar ratio of adsorbed benzene and cyclohexane is estimated to be about 262 at 1:1. The adsorption selectivity of liquid phase benzene / cyclohexane is calculated by the formula (q1 / C2) / (q2 / C1), where q1 and q2 are the adsorption capacities of benzene and cyclohexane, respectively (unit: mmol / g), and C1 and C2 are their molar fractions in the liquid mixture, which are 216, 723 and 1027, respectively (see Fig.15 ), i.e., for mixtures with lower benzene content, the Zn-Ade-TCPE sample even provides higher benzene / cyclohexane adsorption selectivity. The above adsorption selectivity results are the highest benzene / cyclohexane liquid phase adsorption selectivity achieved by solid adsorbents under similar conditions.

[0051] Five consecutive liquid phase adsorption experiments were conducted using the same Zn-Ade-TCPE sample. The experimental results showed that the Zn-Ade-TCPE sample basically maintained good benzene / cyclohexane adsorption selectivity after repeated use. Fig.16 .

[0052] Example 5 Separation test of trace benzene in liquid cyclohexane In order to confirm the ability of Zn-Ade-TCPE samples to capture trace amounts of benzene in liquid cyclohexane, the following experiment was conducted to obtain the liquid phase adsorption isotherm of benzene at room temperature. Zn-Ade-TCPE samples were placed in cyclohexane with initial benzene contents ranging from 10 to 1000 ppm (mass ratio) and the ratio of adsorbent to solvent was 1 g / L. After 12 hours of shaking to reach equilibrium, the benzene content in the mixture was analyzed by gas chromatography-flame ionization detector (GC-FID), and the adsorption capacity was calculated. Fig.17As shown in Figure 2, the amount of benzene adsorption increases sharply when the content is below 100 ppm and reaches a plateau value of 226 mg / g (2.90 mol / g) at about 280 ppm. This liquid phase benzene adsorption is close to the benzene vapor adsorption under low pressure, for example, 229 mg / g (2.93 mol / g) at a pressure close to 28 Pa (see Figure 6 b), which indicates that the pores of Zn-Ade-TCPE are not blocked by liquid cyclohexane.

[0053] To further verify the feasibility of Zn-Ade-TCPE in removing trace benzene in liquid cyclohexane, a Zn-Ade-TCPE sample was placed in a cyclohexane liquid containing 1000 ppm benzene, with an adsorbent to solvent ratio of 10 g / L (adsorbent excess), and the benzene content was monitored while the mixture was shaken. Within the first 2 hours, the benzene content dropped rapidly to 24 ppm, and then further dropped to 7.5 ppm within the next 4 hours (see Fig.18 ), the corresponding benzene removal rate is as high as 99.3%.

[0054] The equivalent of 1L of 99.9% pure cyclohexane (with benzene as impurity) can be deeply purified to >99.999% purity after adsorption and desorption by 10 g of Zn-Ade-TCPE. Similar liquid phase adsorption experiments were also carried out in a 1:99 benzene / cyclohexane liquid mixture with an adsorbent to solvent ratio of 100 g / L. After 6 hours of adsorption, the concentration of benzene dropped to 0.047% (>95% removal), and cyclohexane with a purity of >99.95% was obtained. These results confirm the high performance of Zn-Ade-TCPE in liquid phase benzene / cyclohexane separations, especially in removing trace benzene from cyclohexane.

[0055] Separation mechanism: Cyclohexane molecules cannot enter the large and small pores in the Zn-Ade-TCPE structure, but benzene molecules can. This molecular sieving effect comes from the unique staggered cavity structure of Zn-Ade-TCPE and the subtle differences in the molecular structures of benzene and cyclohexane. The ring molecules are non-planar and significantly thicker than the planar benzene molecules. It is easier for the sheet-like benzene molecules to pass through the narrow gaps between the larger pores in Zn-Ade-TCPE than for the cyclohexane molecules. In addition, for each adsorbed benzene molecule, there are multiple weak CH···π, CH···O (carboxylic acid oxygen atoms) and / or CH···N (adenine N atom) interactions, which act on the framework and adjacent adsorbed benzene molecules. That is, there are abundant weak interactions between the structural framework of Zn-Ade-TCPE and Bz molecules, which should be the reason why Zn-Ade-TCPE can show high Bz adsorption capacity even at low pressure.

Claims

1. Application of a metal organic framework material in removing trace benzene from cyclohexane.

2. The use of the metal organic framework material according to claim 1 in removing trace benzene in cyclohexane, characterized in that: The metal organic framework material is a Zn(II)-based metal organic framework material Zn-Ade-TCPE constructed by mixed ligands, and the chemical formula is C 116 H 96 N 14 O 30 Zn 7, It is a pale yellow block crystalline material prepared by solvent thermal reaction of organic ligand H4TCPE, adenine and Zn(NO3)2·6H2O, wherein H4TCPE is 4,4',4'',4'''-(ethylene-1,1,2,2-tetrayl)tetrabenzoic acid, with molecular formula C 30 H 20 O8.

3. The use of the metal organic framework material according to claim 2 in removing trace benzene in cyclohexane, characterized in that: The molar ratio of adenine, H4TCPE and Zn(NO3)2·6H2O is 1.5:1:2.5, the volume ratio of DMA and water in the mixed solvent is 1:1, and the volume (mL) of the solvent used per millimole of the organic ligand H4TCPE is 1:

60.

4. The use of the metal organic framework material according to claim 2 in removing trace benzene in cyclohexane, characterized in that: The solvent thermal reaction temperature was 120°C and the reaction time was 24 hours.

5. The use of the metal organic framework material according to claim 2 in removing trace benzene in cyclohexane, characterized in that: The method for activating the Zn-Ade-TCPE material is as follows: washing the sample with DMA solvent, then immersing it in methanol solvent, performing solvent exchange for 3-4 times, and then drying the sample immersed in methanol at 60°C, and degassing at 120°C for 8 hours to obtain a dry sample of the material desolvated.

6. The use of the metal organic framework material according to claim 2 in removing trace benzene in cyclohexane, characterized in that: The Zn-Ade-TCPE has a three-dimensional framework structure, which includes chain units formed by the coordination of Zn atoms and N atoms on the adenine ring, and the chain units are connected by deprotonated H4TCPE to form a three-dimensional framework structure; There are two types of holes in the three-dimensional framework structure of Zn-Ade-TCPE, and the holes are connected by extremely narrow pore openings, forming a slit shape.

7. The use of the metal organic framework material according to claim 1 in removing trace benzene in cyclohexane, characterized in that: The metal organic framework material can realize the removal of trace benzene in cyclohexane in gas phase and liquid phase.

8. The use of the metal organic framework material according to claim 1 in removing trace benzene in cyclohexane, characterized in that: The metal organic framework material can be recycled.

9. The use of the metal organic framework material according to claim 1 in removing trace benzene in cyclohexane, characterized in that: The purity of cyclohexane after separation by Zn-Ade-TCPE reaches over 99.9%.

Citation Information

Patent Citations

  • Metal organic framework material for trace BTEX adsorption and preparation method thereof

    CN115558120A

  • Method for separating mixture of benzene, cyclohexane and cyclohexene

    CN115745728A

  • Preparation method of aluminum-based MOF material with high trace benzene adsorption

    CN116804088A

  • Triazene three-dimensional Zn-MOF material and preparation method and application of derivative of triazene three-dimensional Zn-MOF material

    CN117264225A

  • Preparation method of spiral aluminum cluster MOF (Metal Organic Framework) material for separating benzene and cyclohexane

    CN117659425A